Artificial Intelligence Advances in Emerging Dentistry - Alex, Hannah (Current Overview on Science and Technology Research Vol. 10, 2022)
By automating repetitive processes, enhancing diagnosis and treatment planning, and providing more individualized care, artificial intelligence (AI) can completely transform the dentistry industry. One example of AI in dentistry is using machine learning algorithms to predict dental caries (tooth decay). By training a model on a large dataset of dental images and patient information, the algorithm can accurately predict the presence of dental caries in new patients and improve its performance through feature selection and hyperparameter optimization techniques. A visualization tool can help dentists understand and interpret the model's predictions. Overall, AI in dentistry can significantly improve patient care quality while increasing dental procedures' precision and effectiveness.